Peran Sistem Informasi Manajemen Organisasi dalam Pengambilan Keputusan Berbasis Komputer di Rumah Sakit - Agung Wijoyo; Muhamad Yusuf; Dwi Putra Espy Bendanu; Muhammad Adam Febrian; M. Dafit Apriansyah; Muhammad Ilham (Journal of Research and Publication Innovation, 2023)
The hospital as a an institution providing health care for the, there are many funds in the data and information flows during the service.The role of management information system giving information accurate and timely needed to ease the decision making process and solve the organizational problems in decision making based computer that allows the planning function, control, and operational can run effectively at the hospital.This scientific approach in writing descriptive method used a qualitative approach.This research result indicates that development and management of the role of information systems manajamen organization based computer capable of igniting the not only fast and accurate but will also be in line with best practice in the structure of effectively and efficiently.Has been a source of information matters to manage hospitals in the modern world.